The value of adjuvant radiotherapy on survival and recurrence in triple-negative breast cancer: A systematic review and meta-analysis of 5507 patients. (June 2016) - O'Rorke, M.A.; Murray, L.J.; Brand, J.S.; Bhoo-Pathy, N.
Highlights: Few studies have examined the prognostic impact of adjuvant radiotherapy in TNBC. The addition of adjuvant radiotherapy improved locoregional recurrence in TNBC. Adjuvant radiotherapy was not significantly associated with distant recurrence. No consistent overall survival benefit observed between locoregional treatments. Abstract: Background: The value of adjuvant radiotherapy in triple negative breast cancer (TNBC) remains unclear. A systematic review and meta-analysis was conducted in TNBC patients to assess survival and recurrence outcomes associated with radiotherapy following either breast conserving therapy (BCT) or post-mastectomy radiotherapy (PMRT). Methods: Four electronic databases were searched from January 2000 to November 2015 (PubMed, MEDLINE, EMBASE and Web of Science). Studies investigating overall survival and/or recurrence in TNBC patients according to radiotherapy administration were included. A random effects meta-analysis was conducted using mastectomy only patients as the reference. Results: Twelve studies were included. The pooled hazard ratio (HR) for locoregional recurrence comparing BCT and PMRT to mastectomy only was 0.61 (95% confidence interval [CI] 0.41–0.90) and 0.62 (95% CI 0.44–0.86), respectively. Adjuvant radiotherapy was not significantly associated with distant recurrence. The pooled HR for overall survival comparing BCT and PMRT to mastectomy only was 0.57 (95% CI 0.36–0.88) and HR 1.12 (95% CI 0.75, 1.69). Comparing PMRT to mastectomy only, tests for interaction were not significant for stage ( p  = 0.98) or age at diagnosis ( p  = 0.85). However, overall survival was improved in patients with late-stage disease (T3-4, N2-3) pooled HR 0.53 (95% CI 0.32–0.86), and women <40 years, pooled HR 0.30 (95% CI 0.11–0.82). Conclusions: Adjuvant radiotherapy was associated with a significantly lower risk of locoregional recurrence in TNBC patients, irrespective of the type of surgery. While radiotherapy was not consistently associated with an overall survival gain, benefits may be obtained in women with late-stage disease and younger patients.